Implementation of Lean Six Sigma in an Effort to Reduce the Failure of the Pipe Quality Load Test - Mochamad Waras; Wiwik Sulistyowati (Procedia of Engineering and Life Science, 2021)
PT WTUR is a manufacturing whose production is PVC pipe. As a measure to improve quality and optimize work processes in the quality control department. The research aims to minimize the occurrence of impact test failures and provide recommendations for improvement so as to guarantee product quality and generate a sense of satisfaction obtained from consumers. The method used in this research is the lean six sigma method. The purpose of using the lean six sigma method is to reduce waste and determine the causes of the failure of the impact test results. In applying the lean six sigma method, the analysis method is used to determine the causative factors of the root cause using the fishbone diagram and root cause analysis (RCA) and to find out the steps for improvement in reducing the occurrence of load test failures on pipe quality using the failure mode and effect analysis (FMEA).